Explorations in Ethnobiology: The Legacy of Amadeo Rea - Raymond Pierotti (Ethnobiology Letters, 2014)
Review of Explorations in Ethnobiology: The Legacy of Amadeo Rea. Marsha Quinlan and Dana Lepofsky, eds. 2013. Society of Ethnobiology, Denton, TX. Pp. 310, color illustrations, maps, tables. $56.95 (paperback). ISBN 978‐0988733008.